Functional Performance and Associations between Performance Tests and Neurological Assessment Differ in Men and Women with Parkinson’s Disease - Kadri Medijainen; Mati Pääsuke; Aet Lukmann; Pille Taba (Behavioural Neurology)
Background. Neurological assessment of a patient with Parkinson’s disease (PD) is expected to reflect upon functional performance. As women are known to report more limitations even for same observed functional performance level, present study was designed to examine whether associations between neurological assessments and functional performance differ across genders. Methods. 14 men and 14 women with PD participated. Functional performance was assessed by measuring walking speeds on 10-meter walk test (10MWT) and by performing timed-up-and-go-test (TUG). Neurological assessment included Hoehn and Yahr Scale (HY), Movement Disorders Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), Schwab and England Activities of Daily Living Scale (S-E), and Mini Mental State Examination (MMSE). Results. In women with PD, Kendall’s tau-b correlation analyses revealed significant correlations between functional performance tests and neurological assessment measures, with the exception in MMSE. No corresponding associations were found for men, although they demonstrated better functional performance, as expected. Conclusion. Men in similar clinical stage of the PD perform better on functional tests than women. Disease severity reflects upon functional performance differently in men and women with PD. Results indicate that when interpreting the assessment results of both functional performance and neurological assessment tests, the gender of the patient should be taken into consideration.